1974
DOI: 10.1029/ja079i034p05196
|View full text |Cite
|
Sign up to set email alerts
|

‘Hisslers’: Quasi-periodic (T∼ 2 s) VLF noise forms at auroral latitudes

Abstract: The previously reported ‘hissler’ phenomenon has been studied by means of broad band VLF data from antarctic ground stations and from the polar‐orbiting Ogo 2 and Ogo 4 satellites. Hisslers are quasi‐periodic broad band VLF auroral noises that typically present a falling‐tone characteristic on frequency‐time spectrograms and often appear in minute‐long sequences with spacing between individual bursts of the order of 2 s at a given frequency. The falling tones do not usually overlap in time; instead a new one t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
3

Year Published

1994
1994
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(36 citation statements)
references
References 12 publications
2
31
3
Order By: Relevance
“…This example of falling tone chorus is similar to that reported as "hisslers" by Ungstrup and Carpenter [1974] and as magnetospheric line radiation by Neměc et al [2009]. Li et al [2011] conducted a statistical study of the propagation angle and occurrence of falling-tone chorus emissions observed by the THEMIS satellites in the magnetosphere.…”
Section: Falling-tone Emissionssupporting
confidence: 81%
“…This example of falling tone chorus is similar to that reported as "hisslers" by Ungstrup and Carpenter [1974] and as magnetospheric line radiation by Neměc et al [2009]. Li et al [2011] conducted a statistical study of the propagation angle and occurrence of falling-tone chorus emissions observed by the THEMIS satellites in the magnetosphere.…”
Section: Falling-tone Emissionssupporting
confidence: 81%
“…The hisslers presented in this paper are quite similar in the spectral shape observed at the auroral latitudes [ Ungstrup and Carpenter , 1974]. However, the frequency band is different and even the periodicity of hissler element is different.…”
Section: Discussionmentioning
confidence: 54%
“…The falling tones do not usually overlap in time, instead a new one tends to develop as the previous one ends. Hisslers were first noted by Morozumi and Helliwell [1966] and its characteristics have been considered in detail by Ungstrup and Carpenter [1974] using the data of Byrd (geomag. lat., 80°S, long.…”
Section: Introductionmentioning
confidence: 99%
“…QP emissions were further classified into type-I and type-II by Sato et al (1974) on the basis of whether or not they were correlated with geomagnetic pulsations. Hiss-type emissions have been reported which show a degree of periodicity of somewhat shorter periods (from fractions of a second to several seconds), such as 'hisslers' (Ungstrup and Carpenter 1974;Singh et al 2004) and 'pulsing hiss' (Ward et al 1982;Singh et al 2005). These are largely a night phenomenon associated with sub-storm and pulsating aurora respectively (Smith et al 1998).…”
Section: Introductionmentioning
confidence: 96%